Comparing Proton to Photon Radiotherapy Plans: UK Consensus Guidance for Reporting Under Uncertainty for Clinical Trials. Issue 7 (July 2020) - Lowe, M.; Gosling, A.; Nicholas, O.; Underwood, T.; Miles, E.; Chang, Y.-C.; Amos, R.A.; Burnet, N.G.; Clark, C.H.; Patel, I.; Tsang, Y.; Sisson, N.; et al.
Abstract: In the UK, the recent introduction of high-energy proton beam therapy into national clinical practice provides an opportunity for new clinical trials, particularly those comparing proton and photon treatments. However, comparing these different modalities can present many challenges. Although protons may confer an advantage in terms of reduced normal tissue dose, they can also be more sensitive to uncertainty. Uncertainty analysis is fundamental in ensuring that proton plans are both safe and effective in the event of unavoidable discrepancies, such as variations in patient setup and proton beam range. Methods of evaluating and mitigating the effect of these uncertainties can differ from those approaches established for photon therapy treatments, such as the use of expansion margins to assure safety. These differences should be considered when comparing protons and photons. An overview of the effect of uncertainties on proton plans is presented together with an introduction to some of the concepts and terms that should become familiar to those involved in proton therapy trials. This report aims to provide guidance for those engaged in UK clinical trials comparing protons and photons. This guidance is intended to take a pragmatic approach considering the tools that are available to practising centres and represents a consensus across multidisciplinary groups involved in proton therapy in the UK. Highlights: An explanation of the evaluation and reporting of uncertainties in proton planning. A review of current evidence on photon and proton plan comparison. A glossary of terms frequently used in the evaluation of proton plans.